Men's lifestyle and cardiovascular diseases: a health promotion strategy (Research, Society and Development, 2021)
Objectives: to describe the lifestyle of men with cardiovascular disease; to evaluate men’s perceptions of their disease and its prevention approaches; to discuss both men’s health promotion and the prevention of aggravation regarding cardiovascular diseases. Methods: qualitative descriptive study on 22 men in the 25-59 age group presenting any comorbidities associated with cardiovascular diseases. Semi-structured interviewing was employed as the strategy for data collection with the snowball sampling method, a non-probability technique in which research participants recruited other participants. Regarding data analysis, content analysis method was used, a process divided into the following phases: pre-analysis, material exploration and treatment of results, inference and interpretation. Two categories were selected: men’s self-care and lifestyle, and the male perspective on the prevention of cardiovascular diseases. Results and Discussion: the data show that most of the men with cardiovascular diseases have a sedentary lifestyle and that they see self-care as a female concern, resulting in health issues due to the lack of health promotion and disease prevention, what reveals that emergency is the gateway to self-care. Final considerations: it is necessary to invest in health education to bring the basic health care closer to the male population reality using plain language, in addition to training professionals to recruit individuals from this group, thus expanding men’s health care.